The female face of God in Auschwitz : a Jewish feminist theology of the Holocaust - Raphael, Melissa (Routledge, 2003)
The first full-length feminist dialogue with Holocaust theory, theology and social history. Considers women's reactions to the holy in the camps at Auschwitz.
Keywords: Auschwitz (Concentration camp); Holocaust (Jewish theology); Jewish women in the Holocaust.; Presence of God.; Femininity of God.; Holocaust, Jewish (1939-1945) -- Personal narratives -- History and criticism.; Redemption -- Judaism.; Feminism -- Religious aspects -- Judaism.; Holocauste, 1939-1945 -- Aspect religieux -- Judaïsme.; Juives pendant l'Holocauste.; Présence de Dieu.; Dieu -- Féminité.; Holocauste, 1939-1945 -- Récits personnels -- Histoire et critique.; Rédemption -- Judaïsme.; Féminisme -- Aspect religieux -- Judaïsme.; RELIGION -- Judaism -- Theology.; Femininity of God; Feminism -- Religious aspects -- Judaism; Jewish women in the Holocaust; Presence of God; Redemption -- Judaism; Feministische Theologie; Judenvernichtung; Auschwitz; Gott; Deus absconditus; Jüdische Theologie; Alomtegenwoordigheid van God.; Holocaust.; Feministische theologie.; 1939-1945; Criticism, interpretation, etc.; Personal narratives